CDKN2 gene deletion is not found in chronic lymphoid leukaemias of B- and T-cell origin but is frequent in acute lymphoblastic leukaemia - Schröder, Martin; Mathieu-Strauß, Ulrike; Dreyling, Martin H.; Bohlander, Stefan K.; Hagemeijer, Anne; Beverloo, Berna H.; Olopade, Olufunmilayo I.; Stilgenbauer, Stephan; Döhner, Konstanze; Bentz, Martin; Lichter, Peter; Döhner, Hartmut (British journal of haematology, 1995)
Summary. Homozygous deletions of the cyclin-dependent kinase 4 (CDK4) inhibitor gene CDKN2 (pi6, MTS1) have been demonstrated to occur frequently in human cancer cell lines of different origin. However, in most primary tumours the frequencies of CDKN2 deletions are not well defined. We studied primary samples of 100 patients with lymphoid leukaemias [B-lineage acute lymphoblastic leukaemia (ALL), n = 23; T-ALL, n= 7; B-cell chronic lymphocytic (B-CLL) or prolymphocytic (B-PLL) leukaemia, =50; T-CLL/T-PLL, n= 20] using fluorescence in situ hybridization (FISH) with eight overlapping cosmid clones covering the region on chromosome band 9p21 containing CDKN2. We did not observe any CDKN2 deletions in the 70 patients with chronic lymphoid leukaemias of B- or T-cell origin. Of the 23 patients with B-lineage ALL, one (4%) exhibited a CDKN2 deletion: in this patient, two clones were detected, one exhibiting a hemizygous and the other a homozygous deletion. On chromosome banding analysis, four patients with B-lineage ALL had a 9p aberration, whereas all CDKN2 copies were retained. In contrast, six of the seven (86%) patients with T-ALL exhibited CDKN2 deletions (homozygous, n = 4; hemizygous, n = 2). We conclude that hemizygous or homozygous deletions of the CDKN2 gene occur at high frequency in T-ALL and at low frequency in B-lineage ALL, supporting the role of this gene as a tumour suppressor, especially in T-ALL. However, from our data there is no evidence that CDKN2 is involved in the pathogenesis of chronic lymphoid leukaemias of B- or T-cell origin.